The last of the czars shadow of Rasputin (Discovery Channel, 2007)
This episode focuses on Gregory Raputin, a wandering mystic and faith healer who may have had more influence on the Romanovs than many people know. Stories of Rasputin's influence and passionate adoration for the Czarina circulated throughout the country. His influence over Nicholas II was far less, but few believed it. At the same time, the Czar began to retreat from the democracy he's promised. The episode will show how the isolation of the Czar and his wife proceeded apace. As a new wave of discontent grew, the Archduke of Austria was assassinated and Germany declared war. The Czar, who only wanted peace and tranquility, wouldn't see either from his throne again.